2016
DOI: 10.18203/2349-3933.ijam20162509
|View full text |Cite
|
Sign up to set email alerts
|

Candida onychomycosis: Indian scenario

Abstract: Onychomycosis due to Candida species is thought to be restricted to patient with chronic mucocutaneous candidosis (CMC) or as secondary invaders in chronic paronychia. 16 The significance of Candida in the pathogenesis of nail dystrophy ought to be reconsidered as some patients with some forms of nail dystrophy not ABSTRACT Background: Onychomycosis, a fungal infection of nails, may be caused by dermatophytes, nondermatophytes and yeast. Its incidence is progressively increasing, and now it is no more consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Candida strains are known as the important pathological agents of yeast onychomycosis. Similar to other studies conducted in other regions of the world, our study confirmed that onychomycosis was the principal clinical presentation (56.9%) (30)(31)(32). Moreover, this form of infection has been found more often in female than male (33,34).…”
Section: Discussionsupporting
confidence: 90%
“…Candida strains are known as the important pathological agents of yeast onychomycosis. Similar to other studies conducted in other regions of the world, our study confirmed that onychomycosis was the principal clinical presentation (56.9%) (30)(31)(32). Moreover, this form of infection has been found more often in female than male (33,34).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the frequency of NCA species was higher (60.2%) than that of C. albicans (39.8%), indicating an increase in the frequency of NCA species in Iran. While the emergence of NCA species in various regions of the world is pointing towards a varied change in epidemiological behavior of the disease (30), these results in comparison with our previous reports, showed a shift from C. albicans as the predominant pathogen towards an increasing prevalence of the species C. parapsilosis (15). Similar to reports of Ghasemi et al (31) diabetic patients had the highest susceptibility to candidiasis (28.4%).…”
Section: Discussionsupporting
confidence: 62%
“…The identification of bacteria and yeast were done by Vitek-2 (Biomeurix, France) while identification of individual fungi was based on standard methods such as microscopy, morphology, colonial characterization, pigment production, rate of growth and biochemical test. [5][6][7]…”
Section: Methodsmentioning
confidence: 99%